Passing Accuracy Using the Inside and Outside of the Foot in Futsal - Fadhlan Aldiva Suwandi; Komarudin Komarudin; Herdiansyah Agus; Firmansyah Mujahid Fadluloh (Journal Coaching Education Sports, 2026)
This study aimed to examine the effect of structured passing training using the inside and outside of the foot on passing accuracy among futsal athletes. A pre-experimental study employing a One-Group Pretest–Posttest Design was conducted with 20 active Triball FC athletes selected through total sampling. Passing accuracy was measured using a standardized futsal passing and stopping test. The intervention consisted of a six-week training program with three sessions per week, focusing on inside-foot and outside-foot passing drills. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and paired-sample t-tests. The results demonstrated significant improvements in passing accuracy following the intervention. The mean inside-foot passing score increased from 12.60 ± 1.19 to 18.20 ± 1.11 (p < 0.001), while the outside-foot passing score increased from 7.20 ± 1.11 to 14.00 ± 1.41 (p < 0.001). These findings indicate that systematic and progressive passing training effectively enhances technical passing performance in futsal athletes. The study highlights the importance of integrating both inside-foot and outside-foot passing drills into regular training programs, with inside-foot passing serving as the primary technique for accuracy and ball control, while outside-foot passing provides tactical flexibility in dynamic game situations.